Is it Really “Yesterday’s War”? What Gadamer Has to Say About What Gets Counted - Nancy J Moules (University of Calgary, 2017)
In this paper, the authors address the perceived recent trend of funding and publishing bodies that seem to have taken a regard of qualitative research as a subordinate to, or even a subset of, quantitative research. In this reflection, they pull on insights that Hans-Georg Gadamer offered around the history of the natural and human science bifurcation, ending with a plea that qualitative research needs to be received, appraised, judged, and promoted by different lenses and criteria of value.